A prediction model of cognitive impairment risk in elderly illiterate Chinese women - Chen, Zhaojing; Du, Jiaolan; Song, Qin; Yang, Jun; Wu, Yinyin (Frontiers in Aging Neuroscience, 2023)
Objective To establish and validate a targeted model for the prediction of cognitive impairment in elderly illiterate Chinese women. Methods 1864 participants in the 2011–2014 cohort and 1,060 participants in the 2014–2018 cohort from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were included in this study. The Chinese version of the Mini-Mental State Examination (MMSE) was used to measure cognitive function. Demographics and lifestyle information were collected to construct a risk prediction model by a restricted cubic spline Cox regression. The discrimination and accuracy of the model were assessed by the area under the curve (AUC) and the concordance index, respectively. Results A total of seven critical variables were included in the final prediction model for cognitive impairment risk, including age, MMSE score, waist-to-height ratio (WHtR), psychological score, activities of daily living (ADL), instrumental abilities of daily living (IADL), and frequency of tooth brushing. The internal and external validation AUCs were 0.8 and 0.74, respectively; and the receiver operating characteristic (ROC) curves indicated good performance ability of the constructed model. Conclusion A feasible model to explore the factors influencing cognitive impairment in elderly illiterate women in China and to identify the elders at high risk was successfully constructed.